A study of a more general class of nonlocal integro-multipoint boundary-value problems of fractional integro-differential inclusions - Ahmad, B.; Ntouyas, S. K.; Alsaedi, A. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.9 We develop the existence theory for a more general class of nonlocal integro-multipoint boundary value problems of Caputo type fractional integro-differential inclusions. Our results include the convex and non-convex cases for the given problem and rely on standard fixed point theorems for multivalued maps. The obtained results are illustrated with the aid of examples.